PENGARUH KEMAJUAN TEKNOLOGI (SOSIAL MEDIA), LITERASI KEUANGAN TERHADAP MINAT INVESTASI MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - RAHAYU, NILA; ANWAR, ADRIANDA; GENADI, YELDY DWI; PRADNYANI, I GUSTI AGUNG ARISTA (Universitas Mahasaraswati K. Mataram, 2024)
Technology is a symbol of progress in the development of the era. Technology changes the pattern of activities in a person's daily life. Many people use and manage their finances online because of its convenience, starting from savings, buying and selling transactions, In the field of investment, there is a lot of fraud due to lack of knowledge and people who are easily tempted by the returns offered, these reasons underlie the need for each individual to understand financial literacy before taking investment action. The purpose of this study was to examine how Social Media and financial literacy affect investment interest of FEB UNRAM students. With 96 respondents, this study used an associative quantitative methodology using a questionnaire for data collection and SPSS program for data processing. The results showed that financial knowledge and technology (Social Media) have a positive and substantial influence on investment interest. Furthermore, technology and financial literacy factors have an influence of 35% of the total influence, while the rest is influenced by other variables.